Pro‐atherogenic actions of signal transducer and activator of transcription 1 serine 727 phosphorylation in LDL receptor deficient mice via modulation of plaque inflammation. Issue 10 (27th September 2021) - Al‐Ahmadi, Wijdan; Webberley, Thomas S.; Joseph, Alex; Harris, Ffion; Chan, Yee‐Hung; Alotibi, Reem; Williams, Jessica O.; Alahmadi, Alaa; Decker, Thomas; Hughes, Timothy R.; Ramji, Dipak P.
Abstract: Atherosclerosis is a chronic inflammatory disorder of the vasculature regulated by cytokines. We have previously shown that extracellular signal‐regulated kinase‐1/2 (ERK1/2) plays an important role in serine 727 phosphorylation of signal transducer and activator of transcription‐1 (STAT1) transactivation domain, which is required for maximal interferon‐γ signaling, and the regulation of modified LDL uptake by macrophages in vitro. Unfortunately, the roles of ERK1/2 and STAT1 serine 727 phosphorylation in atherosclerosis are poorly understood and were investigated using ERK1 deficient mice (ERK2 knockout mice die in utero ) and STAT1 knock‐in mice (serine 727 replaced by alanine; STAT1 S727A). Mouse Atherosclerosis RT² Profiler PCR Array analysis showed that ERK1 deficiency and STAT1 S727A modification produced significant changes in the expression of 18 and 49 genes, respectively, in bone marrow‐derived macrophages, with 17 common regulated genes that included those that play key roles in inflammation and cell migration. Indeed, ERK1 deficiency and STAT1 S727A modification attenuated chemokine‐driven migration of macrophages with the former also impacting proliferation and the latter phagocytosis. In LDL receptor deficient mice fed a high fat diet, both ERK1 deficiency and STAT1 S727A modification produced significant reduction in plaque lipid content, albeit at different time points. The STAT1 S727A modification additionally caused a significant reduction in plaque content of macrophages and CD3 T cells and diet‐induced cardiac hypertrophy index. In addition, there was a significant increase in plasma IL‐2 levels and a trend toward increase in plasma IL‐5 levels. These studies demonstrate important roles of STAT1 S727 phosphorylation in particular in the regulation of atherosclerosis‐associated macrophage processes in vitro together with plaque lipid content and inflammation in vivo, and support further assessment of its therapeutical potential.